Functional lateralization in auditory cortex under informational masking and in silence - Königs, Liane; Gutschalk, Alexander (European journal of neuroscience, 2012)
The N1m is an evoked magnetic field in auditory cortex that is automatically elicited by tones in silence but not in the context of multiple other tones: when listeners are unaware of a tone stream because of informational masking, no N1m-like activity is observed. In contrast, N1m-like activity is evoked when listeners are aware of the regular tone stream in the same context but in another trial. Here we compared this awareness-related negativity (ARN) with the automatic N1m. First, we evaluated whether stimulus lateralization by ear or interaural time differences modulates hemispheric lateralization of the response, as a putative marker of sensory processing. Second, we evaluated the stimulus-independent hemispheric balance thought to indicate higher level cortical processing. The results dissociate three, partly overlapping, time intervals: the P1m (45-85 ms) was evoked by missed and detected target tones alike. Subsequent negative activity was only observed when listeners indicated awareness of the target stream inside the multi-tone masker. In the N1m time interval (75-175 ms), hemispheric balance of the ARN and N1m was modulated by stimulus lateralization. In the subsequent time interval (175-275 ms), auditory-cortex activity was generally right-lateralized in silence and balanced under informational masking, but was not modulated by stimulus lateralization. These results suggest that the same auditory-cortex activity that varies with perceptual awareness also shows sensory response features. This is in accordance with models for visual perception, suggesting that sensory competition determines whether midlevel visual responses occur automatically or vary with perceptual state.